Brassinosteroids Benefit Plants Performance by Augmenting Arbuscular Mycorrhizal Symbiosis - Ying Ren; Xianrong Che; Jingwei Liang; Sijia Wang; Lina Han; Ziyi Liu; Hui Chen; Ming Tang (Microbiology Spectrum, 2021)
ABSTRACT Arbuscular mycorrhizal (AM) play an important role in improving plant growth and development. The interaction between phytohormones and AM symbiosis is gradually revealed. Here we examined the effect of Brassinosteroids (BR) on AM symbiosis and discussed the synergistic promotion of plant growth by BR and AM symbiosis. The xylophyta Eucalyptus grandis Hill (E. grandis) was inoculated with AM fungi Rhizoglomus irregularis R197198 (R. irregularis) and treated with different concentrations (0, 1, 10, and 100 nM) of 24-epibrassinolide (24-epiBL) for 6 weeks. With the increase of 24-epiBL concentration, E. grandis growth was firstly promoted and then inhibited, but inoculation with AM fungi alleviated this inhibition. 24-epiBL and R. irregularis colonization significantly improved E. grandis growth and antioxidant system response, and the synergistic effect was the best. Compared with the control group, 24-epiBL treatment significantly increased the mycorrhizal colonization and arbuscular abundance of AM fungi R. irregular in E. grandis roots. The expression of AM symbiosis maker genes was significantly increased by 24-epiBL treatment. Both 24-epiBL treatment and AM colonization upregulated gibberellins (GA) synthesis genes, but no inhibition caused by GA levels was found. 24-epiBL is a kind of synthetic highly active BR. Based on the results of 24-epiBL treatment, we hypothesized that BR actively regulates AM symbiosis regulates AM symbiosis without affecting GA-INSENSITIVE DWARF1 (GID1)-DELLA expression. The synergistic treatment of BR and AM symbiosis can significantly promote the growth and development of plants. IMPORTANCE Brassinosteroids (BR) and Arbuscular mycorrhizas (AM) symbiosis play an important role in improving plant growth and development. Previous studies have shown that there is a complex regulatory network between phytohormones and AM symbiosis. However, the interactions of BR-signaling and AM symbiosis are still poorly understood. Our results suggest that BR actively regulates the colonization and development of AM fungi, and AM fungal colonization can alleviate the inhibition of plant growth caused by excessive BR. In addition, BR actively regulates AM symbiosis, but does not primarily mediate gibberellins-DELLA interaction. The synergistic treatment of BR and AM symbiosis can significantly promote the growth and development of plants. The conclusions of this study provide a reference for phytohormones–AM symbiosis interaction.